A Cross-Sectional Study Into the Prevalence of Dairy Cattle Lameness and Associated Herd-Level Risk Factors in England and Wales - Griffiths, Bethany E.; Grove White, Dai; Oikonomou, Georgios (Frontiers in Veterinary Science, 2018)
Lameness is one of the most pressing issues within the dairy industry; it has severe economic implications while causing a serious impact on animal welfare. A study conducted approximately 10 years ago found the within farm lameness prevalence in the UK to be 36.8%. Our objective here is to provide an update on within farm lameness prevalence in the UK, and to provide further evidence on farm level risk factors. A convenience sample of 61 dairy farms were recruited across England and Wales from September 2015 to December 2016. A single farm visit was made and the milking herd was mobility scored, as the cows exited the milking parlor after morning, afternoon, or evening milking. Information regarding the farm and management system was then collected using a short interview with the farmer followed by collection of various subjective and objective measurements of the environment. The same, trained researcher performed all animal and facility-based measures on all visits. A series of univariable analyses were conducted to evaluate the association between various risk factors and herd lameness prevalence (logit transformed). A multivariable linear regression model was then fitted. The median number of milking cows per herd was 193, ranging from 74 to 1,519 cows. The mean within farm lameness prevalence was 31.6%, ranging from 5.8 to 65.4%. In total, 14,700 cows were mobility scored with 4,145 cows found to be lame (28.2%). A number of risk factors were associated with lameness at the univariable analysis level. Categorical risk factors retained in the final model were: resting area type, collecting yard groove spacing width, whether farms were undertaking the 60- to 100-day post calving claw trimming and the frequency of footbathing in the winter. The amount of concentrates fed in the milking parlors or out of parlor feeders was also associated with lameness prevalence. The results of this study have provided an update on the UK herd lameness prevalence and have confirmed the importance of cow comfort and footbathing frequency. The association between early lactation claw trimming and reduced lameness prevalence is, to the best of our knowledge, reported for the first time.